Water Content Comparison of Green Bean and Roasted Bean of Robusta Gumitir Coffee Based on Processing Method and Roast Level - Annisa Lutfi Alwi; Anni Nuraisyah; Zeni Ulma; Lilik Mastutik; Rizky Nirmala Kusumaningtyas (Gontor Agrotech Science Journal, 2023)
This study aims to compare the water content of green beans and roasted coffee bean based on the processing method and roasting level. The research was conducted at the TEFA Coffee Stub-Agricultural Plant Processing Laboratory, Politeknik Negeri Jember in April-July 2022. The coffee samples were Robusta coffee originating from the Gumitir area, Jember. This research consists of two main stages, green bean processing (dry (natural), honey, semi-wet, and full wash process) and roasting process based on light, medium, and dark levels. The analysis result showed that there was a decrease in the water content of coffee beans in each processing method as the roasting level increased. Overall, the water content of roast beans from full wash processing has the highest level compared to roast beans from other processed methods. The water content of green beans was originally 12.65%, decreased to 3.91%, 3.90%, and 3.38% after roasting with light, medium, and dark levels. The darker the roast level, the more weight loss. A significant decrease in water content was obtained in green beans processed by the honey method. Initially, the green bean water content was 13.05%, decreasing to 2.36%, 2.14, and 1.34% at each roasting level. Meanwhile, the green beans produced from natural processing (dry process), semi-wet, and full wash resulted in a decrease in water content that was not significant as the roasting level increased. Based on the results of this study, it is necessary to carry out further research related to the relationship between processing methods and roasting level on the physicochemical characteristics of coffee beans by optimizing.